STRATEGI PENGEMBANGAN USAHA RUMAH TANGGA ABON IKAN TUNA (Thunnus sp.) “BUNDA” - Andi Suci Anita (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2020)
Small and medium industries including household businesses really need to be developed into businesses that are able to develop independently into businesses to increase community income. Household businesses built by the community must of course take into account the potential that can support business continuity. The study was conducted on household businesses Abon Ikan Tuna